Mediterranean diet, lifestyle and quality of life in Sardinian patients affected with Hidradenitis suppurativa - Fernanda Velluzzi; Jasmine Anedda; Silvia Pisanu; Massimo Dell'Antonia; Andrea Deledda; Alessandro Boi; Caterina Ferreli; Laura Atzori (SAGE Publishing, 2021)
Background: Hidradenitis Suppurativa is a chronic inflammatory skin disease with a strong negative impact on physical and psychological health. Obesity, especially visceral adiposity, but also smoking or unhealthy nutritional habits, have been reported to be significantly associated with hidradenitis suppurativa. Design and Method: Case-control study in 35 patients of both sexes affected with hidradenitis suppurativa, and 35 healthy subjects matched for sex, age, and geographic origin (Sardinia, Italy). Results: Several anthropometric measures (body mass index, waist circumference, body composition), lifestyle (Mediterranean diet adherence, and physical activity level), and the perceived physical and mental health status were evaluated in case and controls. Hidradenitis patients showed significantly higher values of body mass index, waist circumference, body composition, fat mass, and lower values of physical and mental health status compared to controls, while both groups showed a similar moderate physical activity level which can be assumed to counteract the negative effects of obesity or poor nutritional pattern in hidradenitis patients. However, none of the evaluated variables were correlated with the severity of the disease, assessed by means of the Hurley stage system or the Sartorius score. Instead, the Sartorius score showed a positive correlation with the duration of hidradenitis, mainly imputable to the diagnostic delay and the consequent long lasting inflammatory status. Conclusions: Although nutritional factors and lifestyle can be important and modifiable factors in the hidradenitis suppurativa course, the detrimental effect of chronic inflammation and delayed management are clearly prevalent and heavily influence the disease burden.